Nephroprotective potential of Pistacia chinensis bark extract against induced toxicity in rats - SAADIA SATTAR; MUHAMMAD RASHID KHAN; NASEER ALI SHAH; FARAH NOUREEN; KIRAN NAZ (Nusantara Bioscience, 2016)
Abstract. Sattar S, Khan MR, Shah NA, Noureen F, Naz K. 2016. Nephroprotective potential of Pistacia chinensis bark extract against induced toxicity in rats. Nusantara Bioscience 8: 192-200. Pistacia chinensis possesses profound antioxidant properties. In this study, the protective influence of P. chinensis bark ethanol extract (PCBE) was scrutinized against CCl4 induced renal toxicity in rats (6 rats in each group). Seven different groups of Sprague–Dawley male rats were intraperitoneally injected with CCl4 (1 mL/kg b.w.; 30% CCl4 in olive oil) at an interval of 48 hour for four weeks. PCBE at doses of 200 and 400 mg/kg b.w. or silymarin at a dose of 100 mg/kg b.w. was orally administered to the animals on alternate days. CCl4 induced renal toxicity was evident by a significant increase in specific gravity, albumin, count of RBCs and pus cells in urine. Administration of PCBE significantly ameliorated the enhanced serum level of urea, creatinine, and bilirubin whereas increased the level of total protein. Moreover, the influence of CCl4 significantly elevated the level of lipid peroxidation (TBARS), H2O2 and nitrite content whereas enzymatic antioxidants (glutathione-S-transferase, glutathione peroxidase, glutathione reductase, catalase, superoxide dismutase, peroxidase, ?-glutamyl transpeptidase, and quinone reductase), non- enzymatic antioxidant reduced glutathione (GSH) content in kidney homogenate was compromised. When animals were treated along PCBE, a remarkable protective role was observed on all the parameters of kidney in comparison to only CCl4 treated groups. From this study, it can be concluded that PCBE holds an effective antioxidant and nephroprotective property.